Ticagrelor vs. clopidogrel in dual antiplatelet therapy after coronary artery bypass surgery: a meta-analysis - Wang, Liyuan; Zhao, Yingying; Zhang, Shijie; Zhang, Tao; Song, Jian; Yun, Yan; Wu, Yi; Wang, Zhengjun; Ma, Xiaochun (Frontiers in Cardiovascular Medicine, 2025)
BackgroundFollowing coronary artery bypass grafting (CABG), the standard treatment regimen typically involves dual antiplatelet therapy (DAPT), which includes a P2Y12 receptor antagonist in combination with aspirin. There is currently no clear consensus regarding the optimal DAPT strategy after CABG. The aim of this meta-analysis was to evaluate and compare the safety and efficacy of ticagrelor vs. clopidogrel in patients post-CABG.MethodsA meta-analysis of eligible studies of patients undergoing CABG and receiving either aspirin plus clopidogrel (A + C) or aspirin plus ticagrelor (A + T) as antiplatelet therapy, was carried out. The outcomes of interest included all-cause mortality, cardiovascular mortality, major adverse cardiovascular and cerebrovascular events (MACCEs), major bleeding, myocardial infarction, stroke, revascularization, saphenous vein occlusion and total graft occlusion.Results4 randomized controlled trials and 3 observational studies (n = 2,424) were eligible for final analysis. A + T was associated with a decreased risk of all-cause mortality (OR = 0.47, 95% CI 0.31–0.70, p < 0.001, p heterogeneity = 0.80, I2 = 0%) and cardiovascular mortality (OR = 0.50, 95% CI 0.31–0.82, p = 0.006, p heterogeneity = 0.71, I2 = 0%), compared with A + C group. No statistically significant difference was found in the rates of major bleeding (OR = 1.16; 95% CI 0.69–1.96; p = 0.57; p heterogeneity = 0.26; I2 = 23%) between two groups. Besides, the rates of MACCEs, myocardial infarction, stroke, total graft occlusion, revascularization and saphenous vein occlusion were comparable between two groups (p > 0.05).ConclusionsThe meta-analysis presented the evidence supporting the use of A + T post-CAVG in reducing all-cause mortality and cardiovascular mortality, with no increase in bleeding events, in comparison with A + C. Additional RCTs are needed to determine the optimal DAPT after CABG.